Rozwiązane

Doprowadź wyrażenia do najprostszej postaci:
a. 2a(3ab -5b)
b. 12(a + 4) – 4 (5 – 3a)
c. -3x (2y – 5 + 2x) + x(6y -12x + 6x)
Proszę o szybką pomoc



Odpowiedź :

SoeCru

a. 2a(3ab -5b)=2a·3ab-2a·5b=6a²b-10ab

b. 12(a + 4) – 4 (5 – 3a)=12a+48-20+12a=12a+12a+48-20=24a+28

c. -3x (2y – 5 + 2x) + x(6y -12x + 6x)=-6xy+15x-6x²+6xy-6x²=

=15x-6x²-6x²=-12x²+15x

Odpowiedź:

a. 2a(3ab-5b)=6a2b-10ab

b. 12(a+4)-4(5-3a)=12a+48-20+12a=28

c. -3x(2y-5+2x)+x(6y-12x+6x)=-6xy+15x-6x2+6xy-12x2+6x2=15x-12x2

licze na naj

Szczegółowe wyjaśnienie: